유사 궤환 선형화에 의한 두 바퀴 구동형 이동 로봇의 추종제어 - 박재용 (The Graduate School, Ajou University, 2006)
This thesis proposes a tracking control method using pseudo-feedback control for two-wheeled mobile robots with nonholonomic constraints. It has been proposed several tracking control method in the existing mobile robots, But the almost method has been showed using with a complex numerical expression with a nonlinear analysis. The purpose of this study was to design for a easier and more simple controller. The problem of the mobile robot moving with a wheel is a nonholonomic strained condition. Thus it has been studied that a lot of study on linearization of the mobile robot with this strained condition. However it was complicated with an analysis of a nonlinear modeling and process design, and the experiment but simulation was very difficult. Thus it used a simple control method in this thesis and verified the proposed Pseudo feedback linearization through realized experiments. Using the method, this thesis result that can remove the complexity, and apply with the designed simple controller on the tracking control in the existing mobile robots
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2006. 2